Professional Readiness of Public Administration Students For Internet of Things-Based Public Service Digitalization: A Case Study of Cahaya Prima University - Muslimin Muslimin (JURNAP: Jurnal Administrasi Publik, 2024)
The acceleration of public service digitalization through Internet of Things (IoT) technology requires future public administrators to possess adequate professional readiness to adapt to emerging technological transformations. This study aims to explore the readiness of Public Administration students at Cahaya Prima University in responding to IoT-based public service digitalization in Bone Regency. A descriptive qualitative approach with a case study design was employed. Data were collected through semi-structured interviews, participant observation, and document analysis involving 12 students who had participated in internships and field practices related to digital public services. The findings reveal that students demonstrate initial readiness, particularly in technical competencies and positive attitudes toward technological innovation. However, significant limitations remain regarding data analysis, ethical awareness, and the ability to translate IoT-generated information into policy recommendations. The interaction among cognitive, affective, and psychomotor dimensions indicates that professional readiness is multidimensional and requires balanced development. The study highlights the importance of integrating IoT literacy, digital ethics, and experiential learning into public administration education. Such integration is essential for preparing adaptive, critical, and responsible future bureaucrats capable of supporting digital governance and smart public service transformation